Profiles of Childhood Trauma in Women With Substance Use Disorders and Comorbid Posttraumatic Stress Disorders - Lotzin, Annett; Grundmann, Johanna; Hiller, Philipp; Pawils, Silke; Schäfer, Ingo (Frontiers in Psychiatry, 2019)
Background Substance abuse and substance dependence are closely related to childhood trauma and posttraumatic stress disorders. Among women with substance use disorders, the majority report physical, sexual or emotional abuse, or neglect. However, it is poorly understood which types of childhood trauma co-occur and how combinations of different types and severities of childhood trauma are related to clinical characteristics. This information is important to inform treatment of women with substance use disorders. Aim The first aim of this research was to investigate profiles of childhood trauma in women with substance use disorders and posttraumatic stress disorders. The second aim was to examine relationships between these childhood trauma profiles and addiction characteristics and current clinical symptoms. Methods We included 343 treatment-seeking women with substance use disorders and comorbid posttraumatic stress disorders according to DSM-IV. Five types of childhood trauma (sexual abuse, physical abuse, emotional abuse, emotional neglect and physical neglect) were measured using the Childhood Trauma Questionnaire. Addiction characteristics were assessed using the Addiction Severity Index-lite. Current severity of clinical symptoms was assessed by the Symptom-Checklist-27. Latent profile analysis was conducted to distinguish profiles of childhood trauma. Analysis of variance was applied to examine the relationship between childhood trauma profiles and addiction characteristics or severity of clinical symptoms. Results Nine out of ten women reported at least one type of childhood abuse or neglect. Four different childhood trauma profiles could be distinguished that characterized different types and severities of childhood trauma: ‘Low trauma’; ‘Moderate sexual and emotional abuse’; ‘Severe sexual and emotional abuse’; and ‘Severe levels of all types of trauma’. Profiles with more severe levels of childhood trauma showed an earlier age at initiation and escalation of substance use. Furthermore, childhood trauma profiles were related to current severity of depressive symptoms, dysthymic symptoms, sociophobic symptoms and distrust. Conclusion In women with substance use disorders and posttraumatic stress disorders, childhood trauma profiles can inform about addiction characteristics and severity of a wide range of clinical symptoms. This information is essential to understand current treatment needs and should be systematically assessed in women with substance use disorders.